BUILDING VOCATIONAL HIGH SCHOOL STUDENTS EMPLOYABILITY SKILLS IN VOCATIONAL EDUCATION WITH AN ARTIFICIAL INTELLIGENCE (AI) APPROACH - Arvieka Sabilla Putri Setiadi; Yoto Yoto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The application of artificial intelligence (AI) in vocational education, particularly in Vocational High Schools (SMK), has a significant impact on improving students' employability skills. This study aims to examine the impact of AI integration in vocational education, focusing on the development of technical skills (hard skills) and interpersonal skills (soft skills). Using a Systematic Literature Review (SLR) approach, this article analyzes various studies discussing the implementation of AI in vocational education, as well as the challenges and opportunities that exist. The findings indicate that AI can improve learning effectiveness through personalized materials, the use of industry-based simulations, and the development of communication and collaboration skills among students. However, challenges faced include limited infrastructure, a lack of technical skills among educators, and resistance to change from schools and students. This study also emphasizes the need for educational policies that support technological development, improve educator skills, and strengthen collaboration between education and industry to create curricula relevant to job market needs, so that vocational high school graduates can compete globally in an increasingly digital world.